Auditor's Competence And Independence As Determinant Audit Quality With Gender As Moderating Variable - I Made Purba Astakoni; Ida Bagus Swaputra; Ni Made Satya Utami; Yenny Verawati (Syntax Corporation Indonesia, 2020)
This study has several objectives: 1) to find out and analyze the effect of auditor competence on audit quality, 2) to know and analyze the effect of auditor independence on audit quality, 3) to know and analyze the role of gender as a moderating effect on the influence of auditor competence on audit quality, 4) to find out and analyze the role of gender as a moderating effect on auditor independence on audit quality. This research was conducted at the Public Accounting Firm (KAP) in Denpasar City. The populations in this study were all auditors in the city of Denpasar, amounting to 112 people. Determination of the sample was done by purposive method, so that the number of samples selected was 53 people. Data collection techniques used was interviews supported by questionnaire with a closed multiple choices. Data analysis used was Partial Least Square (PLS) approach. The results showed that the overall strength of the model was stated to be very good. Hypothesis 1, which states that auditor competence has a significant positive effect on audit quality, can be accepted, Hypothesis 2, which states that auditor independence has a significant positive effect on audit quality, can also be accepted. Through a multi-group analysis it is stated that gender is able to be a moderating variable on the effect of auditor competence over the quality of an audit.Whereas gender testing as a moderating variable on the effect of auditor independence over the quality of an audit has not been tested.